Automated, Miniaturized, and Integrated Quality Control-on-Chip (QC-on-a-Chip) for Cell-Based Cancer Therapy Applications - Wartmann, David; Rothbauer, Mario; Kuten, Olga; Barresi, Caterina; Visus, Carmen; Felzmann, Thomas; Ertl, Peter (Frontiers in Materials, 2015)
The combination of microfabrication-based technologies with cell biology has laid the foundation for the development of advanced in vitro diagnostic systems capable of evaluating cell cultures under defined, reproducible and standardizable measurement conditions. In the present review we describe recent lab-on-a-chip developments for cell analysis and how these methodologies could improve standard quality control in the field of manufacturing cell-based vaccines for clinical purposes. We highlight in particular the regulatory requirements for advanced cell therapy applications using as an example dendritic cell-based cancer vaccines to describe the tangible advantages of microfluidic devices that overcome most of the challenges associated with automation, miniaturization and integration of cell-based assays. As its main advantage lab-on-a-chip technology allows for precise regulation of culturing conditions, while simultaneously monitoring cell relevant parameters using embedded sensory systems. State-of-the-art lab-on-a-chip platforms for in vitro assessment of cell cultures and their potential future applications for cell therapies and cancer immunotherapy are discussed in the present review.